Glyphosate hormesis effects on the vegetative and reproductive development of glyphosate-susceptible and -resistant Conyza sumatrensis biotypes - Cesco, Victor José Salomão [UNESP]; Krenchinski, Fábio Henrique [UNESP]; Rodrigues, Danilo Morilha [UNESP]; Alcántara-de la Cruz, Ricardo [UNESP]; Duke, Stephen O.; Velini, Edivaldo D. [UNESP]; Carbonari, Caio A. [UNESP] (Elsevier, 2024)
Low glyphosate doses that produce hormesis may alter the susceptibility to herbicides of weeds or enhance their propagation and dispersal. The objective of this work was to evaluate the hormetic effects of glyphosate on the vegetative, phenological and reproductive development in resistant (R) and susceptible (S) Conyza sumatrensis biotypes. The glyphosate resistance level of biotype R was 11.2-fold compared to the S biotype. Glyphosate doses <11.25 g ae ha−1 induced temporary and permanent hormetic effects for the number of leaves, plant height and dry mass accumulation up to 28 d after application in both R and S biotypes. The S biotype required 15–19% fewer thermal units at 1.4 and 2.8 g ae ha−1 glyphosate than untreated plants to reach the bolting stage. Also, this biotype had less thermal units associated with the appearance (1225 vs 1408 units) and opening (1520 vs 1765 units) of the first capitulum than the R biotype. In addition, glyphosate affected reproductive traits of both biotypes compared to their controls, increasing the number of capitulum's and seeds per plant up to 37 and 41% (at 2.8 and 0.7 g ae h−1, respectively) in the S biotype, and by 48 and 114% (both at 5.6 g ae ha−1) in the R biotype. Depending on environmental parameters, glyphosate may or may not cause hormetic effects on the vegetative and phenological development of C. sumatrenis biotypes; however, this herbicide increases the speed and fecundity of reproduction, regardless of the glyphosate susceptibility level, which can alter the population dynamics and glyphosate susceptibility of future generations.
Keywords: Flowering; Growth stimuli; Herbicide resistance; Resistance evolution; Seed production; Sumatran fleabane